Acceptable outcomes with unicompartmental knee replacement and PCL deficiency are achievable: a case series of nine patients - Li, P; Kennedy, J; Mohammad, H; Pang, Z; Mellon, S; Jackson, W; Price, A; Dodd, C; Murray, D (Springer, 2020)
Purpose Posterior cruciate ligament (PCL) deficiency is considered to be a contraindication for unicompartmental knee replacement (UKR); however, there is no evidence to support or contradict this. There are occasional circumstances where UKR in PCL deficient patients have been performed where the patient otherwise satisfies the indications for UKR. The aim of this paper is to describe the outcome of UKR in PCL deficient patients.